Pathogen Interactions in Co-infected Wheat Determine Disease Ontogeny and Severity - Abdullah, Araz Sedqi (Curtin University, 2019)
This PhD bridges the gap between the heterogeneity of plant diseases in the field and the emerging field of molecular pathology. It uses a three-way system consisting of the wheat host and two fungi. A range of techniques relating to plant pathology and histology as well as advanced molecular biology and cytology were used. The objective of the thesis was to study disease progress and pathogen interactions in wheat plants co-infected by two major fungi.